2014
DOI: 10.1111/acem.12319
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Point‐of‐care Ultrasonography on Emergency Department Length of Stay and Computed Tomography Utilization in Children With Suspected Appendicitis

Abstract: Objectives: The role of clinician-performed ultrasonography (US) for suspected appendicitis is unclear. Published data conclude that US has high specificity to rule in the diagnosis of appendicitis, with variable sensitivity to rule it out. Newer data suggest that point-of-care (POC) US may have similar test characteristics. Our objective was to evaluate the effect of POC US in children with suspected appendicitis and its effect on emergency department (ED) length of stay (LOS) and computed tomography (CT) uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 31 publications
0
71
0
2
Order By: Relevance
“…3 Frequency of surgically proven appendicitis for each Appy-Score stratum pre-and post-implementation. The numerical percentage value of each bar is given above the bar and the P-value for comparisons between percentages pre-and post-implementation are given for each Appy-Score stratum [14][15][16]. A barrier to more universal adoption of US as a first-line imaging exam for suspected pediatric appendicitis is the perception of increased variability related to provider interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…3 Frequency of surgically proven appendicitis for each Appy-Score stratum pre-and post-implementation. The numerical percentage value of each bar is given above the bar and the P-value for comparisons between percentages pre-and post-implementation are given for each Appy-Score stratum [14][15][16]. A barrier to more universal adoption of US as a first-line imaging exam for suspected pediatric appendicitis is the perception of increased variability related to provider interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the appropriate application of ultrasound in the ED setting can decrease length of stay and improve patient satisfaction [13][14][15][16]. In at least some centers, when emergency physicians directly perform and interpret ultrasound examinations, they achieve faster examination times and increased imaging access at off-hours when radiology-performed ultrasound may not be available [5,[17][18][19][20][21]. To this end, emergency physicians have been actively promoting the expansion of ultrasound services by the specialty by incorporating basic ultrasonography training into residency programs, creating dedicated emergency ultrasound fellowships, and allocating funds toward the acquisition of ultrasound equipment [22,19,[23][24][25]20,26,21].…”
Section: Introductionmentioning
confidence: 99%
“…Sivitz et al [28], with 264 POCUS studies by PEM fellows and attendings, found a sensitivity of 85 % (95 % CI 75–95), specificity of 93 % (85–100), positive likelihood ratio of 11.7 (6.9–20), and negative likelihood ratio of 0.17 (0.1–0.28). Elikashvili et al [29], looking at 150 patients also demonstrated the specificity of PEM-performed POCUS to be 94 % (95 % CI 88–97), indicating that a positive POCUS exam can be acceptable as a rule-in study. They also demonstrated a significantly decreased length of stay for patients with disposition by POCUS compared to radiology (154–288 min) without any cases of missed appendicitis.…”
Section: Diagnostic Applications Of Ultrasoundmentioning
confidence: 99%